Last night at the Telegraph Club - Lo, Malinda (New York : Dutton Books, 2021)
Seventeen-year-old Lily Hu navigates friendship, family, and identity as she discovers her sexuality and falls in love with another girl in 1950s San Francisco$1 (Bs Chinatown.s
Includes author's note.
Keywords: Chinese Americans -- Fiction; Lesbians -- Fiction; Identity (Psychology) -- Fiction; San Francisco (Calif.) -- Fiction. -- History -- 20th century; Young adult fiction